Virulence of Blumeria graminis f. sp. tritici in Brazil, South Africa, Turkey, Russia, and Australia - Kloppe, Tim; Boshoff, Willem; Pretorius, Zacharias; Lesch, Driecus; Akin, Beyhan; Morgounov, Alexey; Shamanin, Vladimir; Kuhnem, Paulo; Murphy, Paul; Cowger, Christina (Frontiers in Plant Science, 2022)
The globally distributed causal agent of powdery mildew on wheat, Blumeria graminis f. sp. tritici (Bgt), is one of the most rapidly adapting plant pathogens and requires monitoring for shifts in virulence to wheat resistance (Pm) genes. Virulence frequencies were assessed in a total of 346 Bgt isolates from several countries that had either lately recorded increasing powdery mildew epidemics (Brazil, South Africa and Australia) or not recently been surveyed (Turkey and Russia). The results were compared to previously published surveys of U.S. and Egyptian Bgt (390 isolates). Many of the Pm genes that have potentially been employed longer (Pm1a – Pm17) were shown to have lost effectiveness, and the complexity of virulence to those genes was higher among Brazilian isolates than those from any other country. Some cases of high virulence frequency could be linked to specific Pm gene deployments, such as the widespread planting of cultivar Wyalkatchem (Pm1a) in Australia. Virulence was also assessed to a set of Pm genes recently introgressed from diploid and tetraploid wheat relatives into a hexaploid winter wheat background and not yet commercially deployed. The isolate collections from Fertile Crescent countries (Egypt and Turkey) stood out for their generally moderate frequencies of virulence to both the older and newer Pm genes, consistent with that region’s status as center of origin for both host and pathogen. It appeared that the recently introgressed Pm genes could be useful sources of resistance in wheat breeding for other surveyed regions.